(untitled) (Andamios, Revista de Investigación Social, 2025)
The argument posits that the recognition of same-sex marriage is not tied to democracy quality or economic development. Enlightenment’s political, social, and economic projects hinge on cis-heteronormative foundations as unquestionable mandates for public life. Analyzing democratic, economic, and human rights indexes against same-sex marriage progress in Latin America and Europe, I argue that favorable indicators do not disrupt sex-gender binary frameworks or heterosexual mandates. LGBT+ rights advancement reflects non-modern logics, resisting marginality post-Cartesian subject production.